Springback prediction of mild steel sheet on L-bending - Che Amir Rajhan, Che Jaffar (2010)
This report deals with deformation analysis of springback in L-bending of sheet metal. Nowadays, many softwares is produced to investigate about the springback in sheet metal bending. These softwares is getting applicable and useful from time to time. Mastering this software will make the industry especially manufacturing industry know the element and condition of materials and appropriate bending process for such material in order to manage the company production cost. This report is done with simulation of springback using a material of Mild Steel on L-bending process and also an experiment of L-bending is conducted using a 1 mm thickness. The springback of Mild Steel sheet was investigated using finite element analysis. Abaqus software is used in this project to simulate the springback of sheet metal in L-bending. The value of 0.5 mm mesh is used for the simulation. In this simulation the die and pressure pad is declared as contact with the workpiece and friction was defined with 0.1. Punch is also declared as contact with the workpiece and it was defined as frictionless. Then the nodes were taken and import to Auto Cad software to measure the angle of springback from the simulation. An experiment of ten specimens of Mild Steel sheet were conducted in this experiment and the result were taken. Thickness of 1 mm was used for the experiment for all specimens. Profile Projector machine is used to measure the angle of the ten specimens. The result from the experiment will be compared to the result of simulation. The result of this report show the springback in simulation 2o and the result of experiment is 2.3o.